Pectin Synthesis and Pollen Tube Growth in Arabidopsis Involves Three GAUT1 Golgi-Anchoring Proteins: GAUT5, GAUT6, and GAUT7 - Lund, Christian Have; Stenbæk, Anne; Atmodjo, Melani A.; Rasmussen, Randi Engelberth; Moller, Isabel E.; Erstad, Simon Matthé; Biswal, Ajaya Kumar; Mohnen, Debra; Mravec, Jozef; Sakuragi, Yumiko (Frontiers in Plant Science, 2020)
The major cell wall pectic glycan homogalacturonan (HG) is crucial for plant growth, development, and reproduction. HG synthesis occurs in the Golgi and is catalyzed by members of the galacturonosyltransferase (GAUT) family with GAUT1 being the archetypal and best studied family member. In Arabidopsis suspension culture cells and tobacco leaves, the Golgi localization of Arabidopsis GAUT1 has been shown to require protein-protein interactions with its homolog GAUT7. Here we show that in pollen tubes GAUT5 and GAUT6, homologs of GAUT7, also target GAUT1 to the Golgi apparatus. Pollen tube germination and elongation in double homozygous knock-out mutants (gaut5 gaut6, gaut5 gaut7, and gaut6 gaut7) are moderately impaired, whereas gaut5-/- gaut6-/- gaut7+/- triple mutant is severely impaired and male infertile. Amounts and distributions of methylesterified HG in the pollen tube tip were severely distorted in the double and heterozygous triple mutants. A chimeric protein comprising GAUT1 and a non-cleavable membrane anchor domain was able to partially restore pollen tube germination and elongation and to reverse male sterility in the triple mutant. These results indicate that GAUT5, GAUT6, and GAUT7 are required for synthesis of native HG in growing pollen tubes and have critical roles in pollen tube growth and male fertility in Arabidopsis.